On spectral theorems for families of linearly connected self-adjoint operators with given spectra associated with extended Dynkin graphs - Ostrovskii, V. L.; Samoilenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We prove spectral theorems for families of linearly connected self-adjoint operators with given special spectra associated with extended Dynkin graphs. We establish that all irreducible families of linearly connected operators with arbitrary spectra associated with extended Dynkin graphs are finite-dimensional.